Analisis Determinan Penghindaran Pajak Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Mahendra Jaya Wardana; Sartika Wulandari (Universitas Sains dan Teknologi Komputer, 2021)
The biggest source of state income from taxes. Indonesian government keep continuously increase the national income through taxes. The research examines how profitability, leverage, independent commissioners and the influence of institusional ownership. The sample used is manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The sampling method uses purposive sampling in order to obtain 58 manufacturing companie. This study uses panel data regression analysis techniques with the help of the Eviews 10. This study shows that the independent variabel profitability has a significant positive effect on tax avoidance. While leverage, independent commissioners, and the influence of institusional ownership has no effect on tax avoidance,